Cannabis Consumption Among Adults Aged 55–65 in Canada, 2018–2021 - Wadsworth, Elle (Journal of drug issues, 2025)
Cannabis consumption among aging adults in Canada is increasing. The aims of the study were to examine cannabis consumption patterns before and after non-medical cannabis legalization and assess whether these patterns differ between men and women. Data were analyzed from Canadian respondents in a repeat cross-sectional survey conducted in 2018–2021. Analyses were conducted among adults aged 55–65 (n = 18,177) who had consumed cannabis in the past 12-month (n = 4119). Past 12-month cannabis consumption significantly increased among 55–65-year-olds from 2018 (19.3%) to the first-year post-legalization in 2019 (24.5%; p < .001), but remained stable thereafter (24.3%, and 25.6% in 2020 and 2021). More men reported past 12-month consumption than women (28.4% vs. 21.4%; p < .001). A substantial number of cannabis consumers consumed to manage a physical or mental health condition. Targeted messaging might be beneficial for this age group, including possible interactions with other medications. This research may be helpful for informing age-adapted cannabis education.